Analisis Keterampilan Proses Sains pada Mata Kuliah Pendidikan IPA: Analysis of Science Process Skills in Science Education Subjects - Rahmaniati, Rita; Aulia, Nadiatun (Anterior Jurnal, 2025)
Science process skills are an inseparable part of science learning. Basic science skills are the foundation for practicing more complex integrated skills. Science process skills are part of the nature of science as a process. Science process skills are essential for prospective teachers in elementary schools because there are science subjects, so science learning is by the nature of science itself. Based on observations in science education courses, it appears that prospective PGSD teachers are still not skilled in KPS. Prospective teachers who are equipped with teaching skills and other skills in learning science will determine how teachers teach science by the nature of science. This study aims to analyze the science process skills of PGSD students at the Faculty of Teacher Training and Education who are taking the Science Education course in the even semester of 2023/2024. The method used in this study is a qualitative method with data collection techniques through Observation, and data analysis using qualitative descriptive. The results of the research show that the dominant science process skills of prospective elementary school teachers can be implemented, namely the skills of observing, classifying, and measuring, while the skills of predicting, communicating, and concluding still need to be trained. It is hoped that prospective teachers who are equipped with good process skills will have an impact on mastering science concepts in their learning so that they can encourage their students' critical thinking and creative writing abilities.